Knowledge of hospital disaster preparedness amongst the emergency department personnel of an academic hospital in Johannesburg, South Africa - Abolarin, Aanuoluwapo Ademola (My University, 2021)
Hospitals play important roles in mitigating the impacts of disaster in a community. In preparing for disasters,the emergency department personnel of a hospital are expectedto know the basic components of the hospital’s disaster protocol or plan. This prospective observational crossectional study sought to assess the knowledge of hospital disaster preparedness amongst the Emergency Department personnel of an academic hospital in Johannesburg, South Africa. A self-administered questionnaire was administered to the stratified and randomly selected sample size of sixty (60) personnel including nurses and doctors with a response rate of 85%. Findings from the study revealed that 74.5% of the personnel knew the hazards that placed the hospital at the risk of implementing its disaster plan, but less than 4% knew the detail of the procedures particularly when deciding to declare or end the disaster plan implementation. A third have had formal training in disaster management while 68.6% were willing to be trained to be more adequately prepared for a disaster operation. There is insufficient knowledge of the disaster plan ofthe hospital selected therefore more education is required. A summary version of the plan may need to be written in order to facilitate memory of the procedures involved.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment for the degree of MMeD Johannesburg, 2021